Study on biodegradation mechanism of Fusarium solani NK-NH1 on the hull wood of the Nanhai No. 1 shipwreck - Wang, Yu; Han, Yeqing; Li, Naisheng; Wang, Cen; Ma, Kaixuan; Huang, Xinduo; Du, Jing; Guo, Hong; Pan, Jiao (Frontiers in Microbiology, 2024)
The Nanhai No. 1 shipwreck is an ancient wooden ship in the Southern Song Dynasty. Currently, serious challenges of microbial diseases exist on the hull wood. This study aimed to obtain microbial samples from the ship hull in December 2021 and analyze the microbial diseases through scanning electron microscopy and high-throughput sequencing to preserve the Nanhai No. 1 shipwreck. The biodegradation mechanism of diseased microorganisms was explored through whole genome sequencing and the detection of enzyme activity and gene expression levels of diseased microorganisms under different conditions. The results showed that there was obvious fungal colonization on the surface of the hull wood and Fusarium solani NK-NH1 was the dominant disease fungus on the surface. NK-NH1 has strong cellulose and lignin degradation ability. Its whole genome size is 52,389,955 bp, and it contains 17402 genes. It has a variety of key enzyme genes involved in cellulose and lignin degradation. The NK-NH1 dominant degrading enzyme lignin peroxidase has the highest enzyme activity at pH=4, NaCl concentration of 30%, and FeSO4 concentration of 50 mg/L, while laccase has the highest enzyme activity at pH=4, NaCl concentration of 10%, and FeSO4 concentration of 100 mg/L. The above research results prove that NK-NH1 is a key fungus to the biodegradation of ship hull wood when it is exposed to air, low pH, high salt, and rich in sulfur iron compounds. This study provides a theoretical basis for the preservation of the Nanhai No. 1 shipwreck.